1999
DOI: 10.1021/jp991964j
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast Infrared Studies of the Reaction Mechanism of Silicon−Hydrogen Bond Activation by η5-CpV(CO)4

Abstract: The photochemical Si−H bond activation reaction by the group VB, d4 organometallic compound η 5 -CpV(CO)4 (Cp = C5H5) has been studied in neat triethylsilane under ambient conditions. The spectral evolutions of the metal-bonded CO stretching bands were monitored from 300 fs to 800 ps following UV photolysis using femtosecond pump−probe spectroscopic methods. The reactive intermediates observed on the ultrafast time scale were also studied using density functional theory as well as ab initio qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
80
1

Year Published

2001
2001
2011
2011

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(89 citation statements)
references
References 54 publications
8
80
1
Order By: Relevance
“…The photochemically induced loss of CO from η 5 -CpM(CO) 3 (M ) Mn, Re), 165a η 5 -CpV(CO) 4 , 141 and M(CO) 6 (M ) Cr, Mo, W), 83 in neat Et 3 SiH under ambient conditions, has been studied with femtosecond pump-probe spectroscopic methods. The studies of the Mn and Re systems have been summarized by Harris and co-workers in an Accounts of Chemical Research article.…”
Section: Carbonyl(s) or Carbonyl Unitsmentioning
confidence: 99%
See 1 more Smart Citation
“…The photochemically induced loss of CO from η 5 -CpM(CO) 3 (M ) Mn, Re), 165a η 5 -CpV(CO) 4 , 141 and M(CO) 6 (M ) Cr, Mo, W), 83 in neat Et 3 SiH under ambient conditions, has been studied with femtosecond pump-probe spectroscopic methods. The studies of the Mn and Re systems have been summarized by Harris and co-workers in an Accounts of Chemical Research article.…”
Section: Carbonyl(s) or Carbonyl Unitsmentioning
confidence: 99%
“…141 Both singlet and triplet CpV(CO) 3 species were formed with different geometries for the two different electronic states (eq 43). The data suggested that the triplet species reacted rapidly through a concerted spin crossover/solvation facilitated by the SiH bond of Et 3 SiH (producing 3-11a).…”
Section: Carbonyl(s) or Carbonyl Unitsmentioning
confidence: 99%
“…Triplet species such as CpV(CO) 3 , CpCo(CO), and Fe(CO) 4 do not form agostic bonds with hydrocarbons and thus tend to react with Si-H bonds to directly form oxidative addition products [59,60]. Perhaps counter intuitively, singlet intermediates such as CpRh(CO) and CpRe(CO) 2 on the average take longer Scheme 6. to form oxidative addition products since they are prone to form modestly stable agostic species with the hydrocarbon moieties in silanes, thus Si-H activation must await rearrangement of these intermediates [61].…”
Section: Oxidative Addition Of C-h Bonds Preceded By Co-lossmentioning
confidence: 99%
“…Pump-probe spectroscopy has been extensively used to understand these types of dynamics [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19], and this work applies the same pump-probe methodologies as well as a relatively new technique, two dimensional infrared spectroscopy, to the photophysics and reactions of several prototypical organometallic complexes [20][21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%